Lateral facial profile may reveal the risk for sleep disordered breathing in children—The PANIC-study. (October 2014) - Ikävalko, Tiina; Närhi, Matti; Lakka, Timo; Myllykangas, Riitta; Tuomilehto, Henri; Vierola, Anu; Pahkala, Riitta
Abstract: Objective. To evaluate the lateral view photography of the face as a tool for assessing morphological properties (i.e. facial convexity) as a risk factor for sleep disordered breathing (SDB) in children and to test how reliably oral health and non-oral healthcare professionals can visually discern the lateral profile of the face from the photographs. Materials and methods. The present study sample consisted of 382 children 6–8 years of age who were participants in the Physical Activity and Nutrition in Children (PANIC) Study. Sleep was assessed by a sleep questionnaire administered by the parents. SDB was defined as apnoeas, frequent or loud snoring or nocturnal mouth breathing observed by the parents. The facial convexity was assessed with three different methods. First, it was clinically evaluated by the reference orthodontist (T.I.). Second, lateral view photographs were taken to visually sub-divide the facial profile into convex, normal or concave. The photos were examined by a reference orthodontist and seven different healthcare professionals who work with children and also by a dental student. The inter- and intra-examiner consistencies were calculated by Kappa statistics. Three soft tissue landmarks of the facial profile, soft tissue Glabella (G`), Subnasale (Sn) and soft tissue Pogonion (Pg`) were digitally identified to analyze convexity of the face and the intra-examiner reproducibility of the reference orthodontist was determined by calculating intra-class correlation coefficients (ICCs). The third way to express the convexity of the face was to calculate the angle of facial convexity (G`-Sn-Pg`) and to group it into quintiles. For analysis the lowest quintile (≤164.2°) was set to represent the most convex facial profile. Results. The prevalence of the SDB in children with the most convex profiles expressed with the lowest quintile of the angle G`-Sn-Pg` (≤164.2°) was almost 2-fold (14.5%) compared to those with normal profile (8.1%) ( p = 0.084). The inter-examiner Kappa values between the reference orthodontist and the other examiners for visually assessing the facial profile with the photographs ranged from poor-to-moderate (0.000–0.579). The best Kappa values were achieved between the two orthodontists (0.579). The intra-examiner Kappa value of the reference orthodontist for assessing the profiles was 0.920, with the agreement of 93.3%. In the ICC and its 95% CI between the two digital measurements, the angles of convexity of the facial profile (G`-Sn-Pg`) of the reference orthodontist were 0.980 and 0.951–0.992. Conclusion. In addition to orthodontists, it would be advantageous if also other healthcare professionals could play a key role in identifying certain risk features for SDB. However, the present results indicate that, in order to recognize the morphological risk for SDB, one would need to be trained for the purpose and, as well, needs sufficient knowledge of the growth and development of the face.